2019
DOI: 10.21037/qims.2018.09.16
|View full text |Cite
|
Sign up to set email alerts
|

Investigating accuracy of 3D printed liver models with computed tomography

Abstract: Background: The aim of this study was to evaluate the accuracy of three-dimensional (3D) printed liver models developed by a cost-effective approach for establishing validity of using these models in a clinical setting.Methods: Fifteen patients undergoing laparoscopic liver resection in a single surgical department were included. Patient-specific, 1-1 scale 3D printed liver models including the liver, tumor, and vasculature were created from contrast-enhanced computed tomography (CT) images using a cost-effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
39
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 29 publications
(32 reference statements)
2
39
0
Order By: Relevance
“…We followed a cost-effective method of developing full-sized 3DP liver models introduced by Witowski et al [13]. Accuracy of this approach has been previously confirmed [14]. Fifteen out of 19 patients have been previously reported in the latter study.…”
Section: Methodsmentioning
confidence: 93%
“…We followed a cost-effective method of developing full-sized 3DP liver models introduced by Witowski et al [13]. Accuracy of this approach has been previously confirmed [14]. Fifteen out of 19 patients have been previously reported in the latter study.…”
Section: Methodsmentioning
confidence: 93%
“…A number of studies have demonstrated encouraging results of the usefulness of 3D printed liver models which serve as valuable tools for pre-surgical planning, intraoperative orientation and simulation purposes (16)(17)(18)(19)(20). However, a recent systemic review highlights the limited studies involving quantitative assessment of the accuracy of 3D printed liver models (21).…”
Section: A B C Dmentioning
confidence: 99%
“…3D printed liver models have been confirmed to overcome limitations of traditional computed tomography (CT) or magnetic resonance imaging (MRI) imaging by providing accurate assessment of complex hepatic anatomy and pathology, and assisting selection of appropriate surgical procedures for hepatic tumors or liver transplantation (16)(17)(18)(19)(20). A recent systematic review has analyzed 19 studies of reporting the usefulness of 3D printed liver models in the simulation of liver surgeries (21).…”
Section: Introductionmentioning
confidence: 99%
“…Of the other 4 original studies, 2 reported the quantitative assessment of model accuracy of liver and biliary anatomical structures and pathologies (23,24). 3D printed models are proved to assist pre-surgical planning and simulation of hepatobiliary disease (25,26), and these two studies offered further evidence of model accuracy in delineating anatomies.…”
mentioning
confidence: 99%
“…3D printed models are proved to assist pre-surgical planning and simulation of hepatobiliary disease (25,26), and these two studies offered further evidence of model accuracy in delineating anatomies. Witowski et al created 15 patientspecific 3D printed liver models including normal hepatic structures and tumours (23). These 3D printed models were CT scanned with analyses compared to those from original CT images in terms of liver parenchyma and tumour volume, as well as diameter and length measurements of hepatic structures.…”
mentioning
confidence: 99%